Preparation method of PAN polymerization liquid intrinsic viscosity and molecular weight test sample

The PAN polymer liquid sample film was prepared by flattening, deionized water rinsing, high-temperature water boiling, multiple rinsing and drying and cooling, which solved the problem of unstable test results caused by the unstable sample preparation, and achieved more accurate and stable intrinsic viscosity and molecular weight testing.

CN119901552APending Publication Date: 2025-04-29FUJIAN ENERGY & PETROCHEMICAL INNOVATION RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411915299.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, when detecting the intrinsic viscosity and molecular weight of PAN polymerization liquid, the sample preparation is not strict, resulting in unstable test results and interference from organic solvents and impurities.

Method used

The sample film is prepared by flattening, rinsing deionized water, boiling with high temperature water, rinsing multiple times and drying and cooling to ensure that the sample is free of organic solvents and impurities.

Benefits of technology

The samples prepared by this method maintain the original characteristics of polymer molecules, eliminate the influence of impurities, and improve the accuracy and stability of the test results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119901552A_ABST
    Figure CN119901552A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a PAN (Polyacrylonitrile) polymer liquid intrinsic viscosity and molecular weight test sample, which is characterized by comprising the following steps of: weighing 2g of PAN polymer liquid, flatly paving the PAN polymer liquid between the opposite surfaces of two flat and clean flat plates, and pressurizing the outer surfaces of the two flat plates under the pressure of not less than 5000Pa for 1 minute; separating the two flat plates, and washing the liquid films on the surfaces of the two flat plates with deionized water until the sample is completely in a white film state; boiling the soft white film in deionized boiling water for 30 minutes; the thin film is taken out and washed with deionized water for three times, and each time is not less than 30 seconds; putting into a clean aluminum foil plate, and drying for 1.5 hours in an electrothermal blowing drying box at 105 DEG C; and cooling the sample membrane in a dryer. The preparation method of the PAN polymerization liquid intrinsic viscosity and molecular weight test sample is reasonable in design, and instability of a detection result caused by organic solvents and impurities in the test sample can be avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a sample, in particular to a method for preparing a sample for testing the intrinsic viscosity and molecular weight of a PAN polymer solution. Background Art

[0002] As a new type of material, PAN-based carbon fiber has high specific strength, high specific modulus, light weight, high temperature resistance, corrosion resistance, and excellent electrical properties. It is widely used in defense, aerospace, energy, transportation, sports, etc. Among them, PAN-based carbon fiber occupies a dominant position in the industrial production of carbon fiber due to its excellent comprehensive properties.

[0003] The polymerization reaction in the carbon fiber production process is a delicate and complex link, which requires precise control of various parameters to ensure the quality of the final product. The quality of the polymerization reaction directly affects the performance of the carbon fiber. If the polymerization is insufficient, the molecular weight of the fiber will be low, which will affect its mechanical strength and heat resistance. If the polymerization is excessive, it may cause the fiber to become brittle, which will also affect its performance. Therefore, the detection of the characteristic viscosity of the polymerization product and the control of the molecular weight are particularly important.

[0004] At present, domestic carbon fiber enterprises use kinematic viscometer and gel permeation chromatography to monitor the intrinsic viscosity and molecular weight in process control, and the sample preparation effect directly affects the accuracy of the test. The polymer solution contains a large amount of solvent, trace water and other impurities. If they are not removed in place during the early sample preparation process, it will directly affect the data, accuracy and stability, and bring harm to production guidance.

[0005] In traditional tests, there are no strict requirements for preliminary sample preparation. After simple rinsing and drying, the sample is dissolved in DMF. This results in unstable test results. The samples contain varying degrees of solvents, trace moisture and impurities that interfere with the test results. Summary of the invention

[0007] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a method for preparing a PAN polymerization liquid intrinsic viscosity and molecular weight test sample, which is reasonably designed and can avoid the instability of the test results caused by organic solvents and impurities in the test sample.

[0008] The present invention provides a method for preparing a PAN polymer solution intrinsic viscosity and molecular weight test sample, which is characterized by comprising the following steps: (1) Weigh 2 g of PAN polymer solution and spread it between the opposing surfaces of two flat and clean plates. Apply a pressure of not less than 5000 Pa to the outside of the two plates for 1 minute. (2) Separate the two plates and rinse the liquid film on the surface of the two plates with deionized water until the sample completely appears as a white film; (3) Boil the soft white film in deionized boiling water for 30 minutes; (4) Take out the film and rinse it with deionized water three times, each time for no less than 30 seconds; (5) Place in a clean aluminum foil tray and dry in an electric heated air drying oven at 105°C for 1.5 hours; (6) Place the sample film in a desiccator to cool.

[0009] Preferably, the length and width of the two flat plates are 15*10CM, the flat plates are stainless steel plates or tempered glass plates, and the pressurizing device is a 7.5KG weight or is manually pressed through a handle on the flat plate.

[0010] Preferably, the deionized water in steps (2) and (3) is laboratory grade water.

[0011] Preferably, during the boiling process, the film is completely immersed in water, and the boiling water used for 2 grams of PAN polymerization solution is not less than 800 milliliters.

[0012] Preferably, the deionized water used for rinsing in the above step (4) is boiling water.

[0013] Preferably, in the above step (5), the film is turned over three times at an average interval during the drying process to ensure sufficient drying.

[0014] Preferably, the two flat plates are 316 stainless steel plates with smooth and clean surfaces and a thickness of not less than 3 mm.

[0015] Preferably, one of the two flat plates is provided with a handle, the handle is in an inverted U shape, both ends of the inverted U shape are fixed to the surfaces of the two flat plates by glue or welding, and the other of the two flat plates is laid on a desktop or platform.

[0016] The sample prepared by flattening, high-temperature boiling, multiple washing, drying and cooling in the present invention maintains the original characteristics of the polymer molecules, removes the organic solvent and impurities therein, and solves the problem of unstable factors brought by the sample preparation stage to the intrinsic viscosity and molecular weight test of the PAN polymer solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 is a flow chart of the sample preparation process of the present invention; Figure 2 , Figure 3 , Figure 4 It is a schematic diagram of the structure of the film pressing device of the present invention; Figure 5 , Figure 6 , Figure 7 The solvent peak spectra after the third flushing of Examples 1-3 are respectively measured by liquid-gas chromatography; Figure 8 is the content of sulfoxide in the second and third rinsing solutions of Example 1, Example 2, and Example 3; Fig. 9 ViscoPump1 is the test result of the sample treated in Example 2; Fig.10 ViscoPump2 is the test result of the sample treated in Example 3; Fig.11 ViscoPump1 and ViscoPump2 are the test results of samples processed in Example 1; Fig.12 It is the summary result of multiple intrinsic viscosity measurements of samples in Examples 1, 2, and 3.

[0020] The central control reset pedal and its combined connection method of the present invention are further described in detail below in conjunction with the accompanying drawings and specific implementation structures. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.

[0022] The specific embodiments of the present invention are as follows: Example 1: Weigh about 2 grams (± 0.2 grams) of polymer liquid and manually spread it on the opposite surfaces of two flat and clean stainless steel plates (or tempered glass plates) with a glass rod. The coating area is about 1 / 2 of the area of ​​the stainless steel plates. Then, the two stainless steel plates are pressurized to more than 5000Pa for 1 minute to make the thickness no more than 50μm so that the liquid film can be fully spread.

[0023] The amount of polymerization liquid should not be too large to prevent it from overflowing the stainless steel pressing plate and being difficult to clean. A 7.5 kg weight is used for pressurization. Manual pressure can also be selected. The duration should be not less than 1 minute so that the flow distribution of the polymerization liquid is thin enough to facilitate the cleaning of the organic solvent therein.

[0024] Then separate the stainless steel plates and rinse the liquid film with deionized water until the sample completely appears as a white film.

[0025] Then use tweezers to clamp the prepared film into boiling deionized water and cook it for 30 minutes, ensuring that the film is completely immersed in the boiling water (no less than 800 ml of boiling water is used for 2 grams of PAN polymerization solution); continuous boiling in high-temperature boiling water has a much greater effect on the precipitation of organic solvents in the polymerization solution than immersion in cold water.

[0026] Thereafter, the film was taken out of the boiling water, and rinsed with three bottles of freshly boiled deionized water for more than 30 seconds respectively; the film was placed in a clean aluminum foil tray, and dried in an electric heated blast drying oven at 105° C. for 1.5 hours, and then the sample film was placed in a dryer to cool.

[0027] One of the two flat plates 1 is provided with a handle 2, which is in an inverted U shape, and both ends of the inverted U shape are fixed to the surfaces of the two flat plates by glue or welding, and the other of the two flat plates is laid on a desktop or platform.

[0028] Example 2: Weigh about 2 grams of polymer solution and manually spread it on the opposite surfaces of two flat and clean stainless steel plates (or tempered glass plates) with a glass rod. The coating area is about 1 / 2 of the area of ​​the stainless steel plates. Then, pressurize it to more than 5000 Pa for 1 minute.

[0029] Then separate the stainless steel plates and rinse the liquid film with deionized water until the sample completely appears as a white film.

[0030] Place the prepared film in water at room temperature for 12 hours, and ensure that the film is completely immersed in the water (no less than 800 ml of boiling water is used for 2 grams of PAN polymerization solution).

[0031] The film was taken out and rinsed with three bottles of fresh deionized cold water for more than 30 seconds respectively; then, it was placed in a clean aluminum foil tray and dried in an electric heated air drying oven at 105° C. for 1.5 hours, and then the sample film was placed in a dryer to cool.

[0032] Example 3: Weigh about 2 grams of polymer solution and manually spread it on the opposite surfaces of two flat and clean stainless steel plates (or tempered glass plates) using a glass rod, add a 4.5 kg weight, and the pressure is about 3000 Pa.

[0033] The liquid film spread by the stainless steel rod was rinsed with deionized water until the sample completely appeared as a white film; the thickness of the film was greater than that of Example 1 and Example 2.

[0034] The prepared film was clamped with tweezers and placed in boiling deionized water for 30 minutes, ensuring that the film was completely immersed in the boiling water.

[0035] Take out the film from the boiling water and rinse it with three bottles of fresh boiled deionized water for more than 30 seconds respectively.

[0036] Place the sample in a clean aluminum foil tray and dry it in an electric forced air drying oven at 105°C for 1.5 hours. Then place the sample film in a desiccator to cool.

[0037] The solvent content of the second and third rinse solutions in Examples 1-3 was tested. Figure 8 As shown in the test results, the sample of Example 1 of the present application did not detect solvent in the third rinse solution, while the second and third rinse solutions of Examples 2 and 3 contained different degrees of solvent residues. The sample of Example 1 of the present application also detected solvent in the second rinse solution. The specific test results of the third rinse solution of each example are shown in Figure 5 , 6 and 7. The impurity treatment effect of Example 1 of the present application is significantly better than that of other examples.

[0038] In the preparation process of Example 3, the pressure was about 3000Pa, and the film thickness was 4000 Pa. Samples of the same mass were weighed, dissolved with DMF, and oscillated and dissolved under the same temperature and time (90°C, 2h). Example 1 showed clear and transparent dissolution under strong light, while Example 3 showed slightly insoluble matter under strong light, proving that it was not completely dissolved under this condition.

[0039] The samples containing sulfoxide (Example 2, Example 3) have the risk of unstable test results in the intrinsic viscosity test; while in Example 1, the samples with more thorough solvent treatment have been verified many times in the specific viscosity test, and the test results are highly stable, which can significantly improve the detection efficiency and accuracy. Fig.12 .

[0040] The method of the present invention utilizes the principle that the polymerization liquid solvent and water are mutually miscible, and spreads the sample in an extremely thin form on a flat and clean plane (ensuring that the thickness is not more than 50 μm, and at a temperature above 20° C., a pressure of not less than 5000 Pa is applied for 1 minute), and then is made into a solid film through the steps of rinsing with deionized water, boiling, washing, drying, drying and cooling. The sample prepared by the method is thin and clean, does not contain relevant organic solvents and water, and thus does not affect the test result of the next step. In the subsequent viscosity and molecular weight test, the required mass is weighed with a precision electronic balance, and DMF is used for shaking dissolution and filtration at the required temperature to prepare a solution of the required test sample. The advantage of the present invention is that the influence of impurities is further eliminated, the form and characteristics of the molecular weight of the polymerization liquid are completely preserved, and the test result is more accurate and reliable.

[0041] The samples prepared in the present invention are not only used for the detection of intrinsic viscosity, molecular weight and molecular weight distribution, but are also not limited to the preparation of PAN polymer solution. The preparation method of the same type of samples is also within the protection scope of this invention.

[0042] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention.

Claims

1. A method for preparing a PAN polymer solution intrinsic viscosity and molecular weight test sample, characterized in that: The steps include: (1) Weigh 2 g of PAN polymer solution and spread it between the opposing surfaces of two flat and clean plates. Apply a pressure of not less than 5000 Pa to the outside of the two plates for 1 minute. (2) Separate the two plates and rinse the liquid film on the surface of the two plates with deionized water until the sample completely appears as a white film; (3) Boil the soft white film in deionized boiling water for 30 minutes; (4) Take out the film and rinse it with deionized water three times, each time for no less than 30 seconds; (5) Place in a clean aluminum foil tray and dry in an electric heated air drying oven at 105°C for 1.5 hours; (6) Place the sample film in a desiccator to cool.

2. The method for preparing a PAN polymer solution intrinsic viscosity and molecular weight test sample according to claim 1, characterized in that: The length and width of the two flat plates are 15*10CM, the flat plates are stainless steel plates or tempered glass plates, and the pressurizing device is a 7.5KG weight or is manually pressed through handles on the flat plates.

3. The method for preparing a PAN polymer solution intrinsic viscosity and molecular weight test sample according to claim 1 or 2, characterized in that: The deionized water described in steps (2) and (3) is first-class laboratory water.

4. The method for preparing a PAN polymer solution intrinsic viscosity and molecular weight test sample according to claim 3, characterized in that: During the boiling process, the film is ensured to be completely immersed in water, and the boiling water used for 2 grams of PAN polymerization solution is not less than 800 milliliters.

5. The method for preparing a PAN polymer solution intrinsic viscosity and molecular weight test sample according to claim 4, characterized in that: The deionized water used for rinsing in step (4) is boiling water.

6. The method for preparing a PAN polymer solution intrinsic viscosity and molecular weight test sample according to claim 5, characterized in that: In the step (5), the film is turned over three times at an average interval during the drying process to ensure sufficient drying.

7. The method for preparing a PAN polymer solution intrinsic viscosity and molecular weight test sample according to claim 1, characterized in that: The two flat plates are 316 stainless steel plates with smooth and clean surfaces and a thickness of not less than 3 mm.

8. The method for preparing a PAN polymer solution intrinsic viscosity and molecular weight test sample according to claim 2, characterized in that: One of the two flat plates is provided with a handle which is in an inverted U shape, and both ends of the inverted U shape are fixed on the surfaces of the two flat plates by glue or welding, and the other of the two flat plates is laid on a desktop or platform.

Citation Information

Cited By

  • Method for testing performance of polymer liquid

    CN120609702A